7. Software Evaluation Criteria and Terminology - Belyk, Diane; Feist, David (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
This report discusses issues of software selection and terminology, highlighting terms that are useful in evaluation studies. A framework for the evaluation of educational software is presented. Links are cited at the end of this article to the American Society for Training & Development (ASTD), and CNET Network’s glossaries of terminology relating to online collaborative methods.